AB0057 Serum IL-16 Concentration Markedly Decreases following Methotrexate and IL-6 Receptor Inhibition Treatment in Patients with Rheumatoid Arthritis. (10th June 2014) - Murota, A.; Suzuki, K.; Kassai, Y.; Miyazaki, T.; Morita, R.; Yoshimura, A.; Takeuchi, T.
Abstract : Background: High-throughput serum protein screening by nucleic acid aptamers identified interleukin 16 (IL-16) as an up-regulated cytokine whose levels positively correlate with those of serum MMP-3 in patients with untreated rheumatoid arthritis (RA) compared to healthy volunteers. IL-16, which binds to CD4 expressed on T lymphocytes, macrophages, dendritic cells and eosinophils, is a chemoattractant factor that evokes massive infiltration of mononuclear cells in the synovial tissue in RA [1]. Although synovial and serum concentrations of IL-16 are significantly elevated in RA [2], the clinical significance of this increase remains unclear. Objectives: We investigated the association of IL-16 in RA patients treated with methotrexate (MTX) and biologics with clinical disease activity markers. Methods: Serum IL-16 concentrations in consecutive RA patients at our institution who had not been treated with MTX or biologics were measured by ELISA. Age- and sex-matched healthy volunteers were used as controls. All patients fulfilled either the 1987 and/or 2010 rheumatoid arthritis classification criteria. In patients, concentrations were measured at baseline and 12 weeks after treatment with MTX or biologics. In biologics therapy, patients who started with MTX at baseline or whose MTX dosage was gradually increased during the 12 weeks were excluded. Statistical analysis between concentrations and clinical parameters was done. Results: 83 RA patients (Table 1 ) and 30 healthy controls (HC) were enrolled. Average IL-16 concentration of RA patients was 176.9 pg/ml, significantly higher than that of HC (141.8 pg/ml, p=0.014). Cut-off value was 155.7 pg/ml (sensitivity 0.67, specificity 0.6, AUC 0.72). Serum IL-16 concentrations at 12 weeks were significantly decreased (pretreatment: 188.7 pg/ml, posttreatment: 155.4 pg/ml, p=1.25E-07). On stratification by treatment, MTX (171.5 pg/ml, 128.8 pg/ml, p=9.27E-05) and IL-6 receptor blockade with tocilizumab (222.1 pg/ml, 177.3 pg/ml, p=0.002) or CTLA4-Ig (abatacept) (239.3 pg/ml, 199.7 pg/ml, p=0.042) for 12 weeks showed a similar tendency, whereas TNF blockade with infliximab (155.0 pg/ml, 146.5 pg/ml, p=0.226) did not. In comparison to clinical parameters, such as DAS28-CRP and SDAI, serum MMP-3 andΔMMP-3 were more highly correlated with serum IL-16 level (r=0.41) and ΔIL-16 with treatment (r=0.37). Conclusions: In this study, MTX and IL-6 receptor inhibition treatment for RA caused a marked decrease in serum IL-16 concentration, while CTLA4-Ig caused a mild decrease. Among clinical parameters, MMP-3 levels were well correlated with IL-16, suggesting that IL-16 might reflect synoviocyte proliferation in RA. References: Kirwan JR, et al. Arthritis Rheum 2004;50:1-4 Lard LR, et al. J Rheumatol 2004;31:35-39 Disclosure of Interest: A. Murota: None declared, K. Suzuki: None declared, Y. Kassai Employee of: Takeda Pharmaceutical Company Limited, T. Miyazaki Employee of: Takeda Pharmaceutical Company Limited, R. Morita: None declared, A. Yoshimura: None declared, T. Takeuchi Grant/research support: Abbott Japan Co., Ltd., Astellas Pharma, Bristol–Myers K.K., Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Sanofi–Aventis K.K., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., and Teijin Pharma Ltd., abbvew GK, Asahikasei Pharma Corp., Taisho Toyama Pharmaceutical Co., Ltd. speaking fees from Abbott Japan Co., Ltd., Bristol–Myers K.K., Chugai Pharmaceutical Co, . Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., and Takeda Pharmaceutical Co., Ltd., Astellas Pharma, Diaichi Sankyo Co., Ltd. and consultant fees from Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., and Asahi Kasei Medical K.K., abbivie GK, Daiichi Sankyo Co., Ltd. DOI: 10.1136/annrheumdis-2014-eular.1074